PARADOKS PEMBANGUNAN DAN KRISIS PERLINDUNGAN LINGKUNGAN - Nida Silvia Lestari; Syarkawi Syarkawi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Economic development in developing countries, including Indonesia, faces a fundamental paradox between the pursuit of economic growth and the escalating crisis of environmental protection. Development strategies that prioritize economic expansion, natural resource exploitation, and accelerated investment have contributed significantly to environmental degradation, such as deforestation, pollution, and the increasing frequency of ecological disasters. This condition reflects a persistent gap between normative commitments to sustainable development and actual policy implementation. This study aims to analyze the development paradox and environmental protection crisis in Indonesia from the perspective of public policy and environmental governance. The research employs a qualitative approach using a literature review method, examining academic journals, policy documents, and official reports from national and international institutions. Data are analyzed through thematic content analysis to identify key patterns and structural issues within development and environmental policies. The findings indicate that Indonesia’s environmental protection crisis is structural in nature, driven by weak law enforcement, overlapping regulations, limited institutional coordination, and largely formalistic public participation. This development paradox has resulted in heightened socio-ecological risks and environmental injustice. The study emphasizes the necessity of reorienting development paradigms toward an integrative sustainable development approach, where strengthened environmental governance becomes a fundamental prerequisite for long-term welfare sustainability and social equity in Indonesia.Keywords: development paradox, environmental protection, public policy, environmental governance, Indonesia.